Rocket writes a story [book with audioplayer] - Hills, Tad (Schwartz & Wade Books, 2024)
Rocket loves books and he wants to make his own, but he can't think of a story. Encouraged by the little yellow bird to look closely at the world around him for inspiration, Rocket sets out on a journey. Along the way he discovers small details that he has never noticed before, a timid baby owl who becomes his friend, and an idea for a story.